2017
DOI: 10.1111/1556-4029.13525
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Acute Hemorrhagic Bowel Infarction Caused by Mesenteric Venous Thrombosis

Abstract: Acute mesenteric venous thrombosis (MVT) is a rare, but life-threatening medical phenomenon. MVT is normally characterized by insidious onset, with nonspecific signs and symptoms. A high index of clinical suspicion is required for diagnosis, and emergency surgery is necessary to optimize the chances of patient survival, especially in the people aged more than 70 years. Surprisingly, based on my review of the literature, no fatal acute MVT case has been reported in the forensic literature. All reported such cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(77 reference statements)
1
0
0
Order By: Relevance
“…( 29 , 30 ). The association between higher D-dimer level and intestinal ischemia has been reported previously ( 26 , 29 , 31 ). Our study likewise demonstrated that D-dimer had a significant positive correlation with intestinal resection (OR = 1.128; 95% CI, 1.005–1.267; p = 0.040) in univariable analysis, whereas no significant difference was observed in the multivariate analysis.…”
Section: Discussionsupporting
confidence: 76%
“…( 29 , 30 ). The association between higher D-dimer level and intestinal ischemia has been reported previously ( 26 , 29 , 31 ). Our study likewise demonstrated that D-dimer had a significant positive correlation with intestinal resection (OR = 1.128; 95% CI, 1.005–1.267; p = 0.040) in univariable analysis, whereas no significant difference was observed in the multivariate analysis.…”
Section: Discussionsupporting
confidence: 76%